Synergetic pore structure optimization and nitrogen doping of 3D porous graphene for high performance lithium sulfur battery. (March 2019) - Cheng, Dongdong; Wu, Pingping; Wang, Jingwen; Tang, Xingwei; An, Tong; Zhou, Han; Zhang, Di; Fan, Tongxiang
Abstract: Synthesis of multifunctional sulfur host material with comprehensive abilities of sulfur accommodation, electron/ion transfer and polysulfides confining is vital and challenging to bring the theoretical merits of lithium sulfur battery to practical application. Herein, a facile strategy is demonstrated to prepare 3-dimensional hierarchical porous nitrogen doped graphene as a sulfur host material for lithium sulfur battery, where urea is employed as both nitrogen doping source and self-removed template for pore structure optimization. The resultant material possesses high nitrogen doping content, 3-dimentional interconnected hierarchical porosity and conductive network and robust mechanical structure, which give rise to a comprehensive ability for multiscale electron/ion transfer, sulfur accommodation and polysulfides confining. Benefiting from the rational structure design, the sulfur loaded composite exhibits high sulfur utilization (1311 mA h g −1 at 0.2 C), high rate capability (950, 762 and 580 mA h g −1 at 1, 2 and 3 C respectively) and excellent cycling stability with high sulfur mass loading (714 mA h g −1 at 1.5 mA cm −2 after 400 cycles for a sulfur loading of 4 mg cm −2 ). The outstanding electrochemical performance, scalable fabrication process, and compatibility with industrial slurry-coating process makes it an ideal host material for practical application of lithium sulfur battery. Graphical abstract: